Analisis Pelaksanaan Pernikahan Wanita Hamil Diluar Nikah Kompilasi Hukum Islam Pasal 53 - Raudhinaa Gumilar Tauzirie; Amalia (STAI Al-Mas'udiyah, 2022)
This research is motivated by the stipulation of article 53 of the KHI which allows pregnant women to marry men who impregnate them and without waiting for the birth of a baby. This research is a qualitative research in which data collection is carried out using the library method. While the analysis process is carried out by basing on the qualitative descriptive analysis method. The results of this study are the provisions in article 53 of the KHI are aPregnant women out of wedlock can be married to men who impregnate them, without having to wait for the birth of their child and no need for remarriage after the child is conceived and the stipulation in Article 53 KHI concerning When a pregnant woman marries a pregnant woman, it is concluded that the maslahah contained in the article is to provide convenience and relief in the case of marrying a pregnant woman in the form of accountability for the actions taken, as well as covering the disgrace so that honor is maintained and biological lineage is maintained so that in administrative management it is notconstrained.